2022
DOI: 10.1155/2022/7913025
|View full text |Cite
|
Sign up to set email alerts
|

Application Value of Combined Detection of NLR, PNI, D-Dimer, CD3+ T Lymphocytes, and CEA in Colorectal Cancer Screening

Abstract: Objective. To investigate the application value of combined detection of neutrophil-lymphocyte ratio (NLR), prognostic nutrition index (PNI), D-dimer (D-D), CD3+ T lymphocytes (CD3+ T), and carcinoembryonic antigen (CEA) in colorectal cancer screening. Methods. The study cohort comprised 187 colorectal cancer patients and 100 mixed hemorrhoids patients as controls from January 2019 to August 2021 at the Fifth Affiliated Hospital of Sun Yat-sen University. Comparing the levels of NLR, PNI, D-D, CD3+ T, and CEA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies show that the cancer antigen (CA 15.3) is used to monitor response to breast cancer treatment and disease recurrence, although the diagnostic threshold varies according to the laboratory and the kit used, data from the present study corroborate with those found in the literature, where we observed a high incidence of breast cancer in women, although CA 15.3 has not been used specifically for breast cancer screening, it can be implemented to reduce costs and high risks with mammography at these ages. A recent study showed that the combination of neutrophil lymphocytes (NLR), prognostic nutritional index (PNI), D-dimer (D-D), CD3+ T lymphocytes (CD3+ T) and CEA has a high clinical application value for colorectal cancer and can provide a reference for early screening and auxiliary diagnosis of colorectal cancer [60]. CEA is the most widely used tumor marker for clinical screening and diagnosis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the cancer antigen (CA 15.3) is used to monitor response to breast cancer treatment and disease recurrence, although the diagnostic threshold varies according to the laboratory and the kit used, data from the present study corroborate with those found in the literature, where we observed a high incidence of breast cancer in women, although CA 15.3 has not been used specifically for breast cancer screening, it can be implemented to reduce costs and high risks with mammography at these ages. A recent study showed that the combination of neutrophil lymphocytes (NLR), prognostic nutritional index (PNI), D-dimer (D-D), CD3+ T lymphocytes (CD3+ T) and CEA has a high clinical application value for colorectal cancer and can provide a reference for early screening and auxiliary diagnosis of colorectal cancer [60]. CEA is the most widely used tumor marker for clinical screening and diagnosis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, D-dimers have been found to reflect fibrinolysis and activation of the coagulation cascade. For example, studies have shown that D-dimer can be used as a prognostic marker for tumor indications in colorectal, 12 lung, 13 liver, 14 ovary, 15 and gastric cancer progression. 16 The platelet count is another widely used marker that can be easily obtained from the parameters of whole blood cells.…”
Section: Introductionmentioning
confidence: 99%